Políticas educacionais para o enfrentamento do analfabetismo de jovens e adultos nos municípios do extremo norte do Bico do Papagaio: intenções e realidade - Silva, Walisson Mariano Carvalho (Universidade Federal do Tocantins, 2021)
The finding of a high rate of illiterates aged 15 years and over, in a country that since 1988 formally guarantees the right to education to these people outside school age, contributed to the development of the research that starts with the following problem: which are the public educational policies developed to confront illiteracy among young people and adults in the counties s of the extreme north of the parrot's beak? The investigation of this problem has as general objective to know the policies of education proposed and carried out by the public power to confront the illiteracy of young people and adults in the counties of the extreme north of Bico do Papagaio, in the state of Tocantins. To achieve this, the research will be guided by the specific objectives of estimating the percentage of absolute illiterates aged 15 years or over; to verify the amount of primary school enrollment, under the responsibility of the counties, in the school census, after the 2010 census illiteracy rate was disseminated, of the counties in the extreme north of the Bico do Papagaio; Identify goals and strategies aimed at confronting illiteracy among youth and adults in Municipal Education Plans (2015-2025); analyze the results of evaluation reports and monitoring of these goals and strategies of the Municipal Education Plans (2015- 2025). For the organization and analysis of the data the documentary analysis technique was used to interpret, synthesize the information and the content analysis for the realization of the inferences. As an aid to the analysis of the reports, it was verified the amount of enrollment of the elementary school of the modality of Education Young and adults, under municipal responsibility. The monitoring and evaluation reports of the plans were taken from the website of PNE em Movimento, as a public document. The results show that in the municipalities of the extreme north of the Bico do Papagaio, permeated by social and educational inequalities, prevails the disarticulation between the policies of refraining from the illiteracy of young people and adults, the BLP and the MEP. This, despite being a decade and still in its third year, strategies need to be developed urgently so that the plan can be materialized.